Difficulties in the differential diagnosis of focal lung lesions in a patient with rheumatoid arthritis who has received anti-B-cell therapy with rituximab. Description of a clinical case - M. D. Suprun; P. A. Sholkina; L. A. Semyonova; L. P. Ananyeva (Современная ревматология)
We present a clinical case of a patient treated with rituximab and methotrexate for rheumatoid arthritis with progressive focal lung lesions that were difficult to interpret. The complexity of the problem of focal lung lesions in rheumatic diseases, which involves a broad spectrum of clinical medical disciplines, is emphasized.